SULING BAMBOO MUSIC: THE IDENTITY OF TIMOR TENGAH UTARA SOCIETY - Yohanis Devriezen Amasanan; Kadek Paramitha Hariswari; Stanislaus Sanga Tolan (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
Suling bamboo music is a traditional music typical of the people of Timor Tengah Utara (TTU) Regency. The musical form of the suling bamboo is very unique and different from the form of the suling bamboo that exists in all regions in Indonesia. The purpose of this study is related to the problem raised, namely to reveal the problem of form and musical elements that make up suling bamboo in Timor Tengah Utara (TTU) Regency. The method used in this research is qualitative analytical method. Data collection techniques were carried out using observation techniques, interview techniques and document study techniques. The results of the study show the following. First, the musical elements that make up the suling bamboo music are as follows. Rhythm, compositionally the rhythm/rhythm of suling bamboo music is a typical Timor rhythm. Melody, on the suling the song plays the main melody or Cantus Frimus (cf), while the trumpet and bass suling play a filler melody or fill melody according to chords. Harmony, which functions to play chords, namely the suling trumpet and the suling bass. Tempo, in the Suling bamboo music game, is very relative depending on the song being sung, which is often used is the tempo of Adate: MM 72-76, Adantino: MM 80-84 and Moderato: MM 90-104. This research can broaden the reader's perspective on the existence of Suling bamboo music and provide information about the forms and musical elements that make up bamboo flute music in Timor Tengah Utara (TTU) RegencyKeywords: Suling bamboo music; musical forms; elements AbstrakMusik suling bambu merupakan musik tradisional khas masyarakat Timor Tengah Utara (TTU). Bentuk musik suling bambu sangat unik dan berbeda dengan bentuk suling bambu yang ada di seluruh daerah di Indonesia. Tujuan penelitian ini berkaitan dengan masalah yang diangkat yakni mengungkap masalah bentuk serta unsur-unsur musikal yang membentuk musik suling bambu di Kabupaten Timor Tengah Utara (TTU). Metode yang digunakan dalam penelitian ini adalah metode kualitatif analitikal. Teknik pengumpulan data dilakukan dengan menggunakan teknik observasi, teknik wawancara dan teknik studi dokumen. Hasil penelitian menunjukan sebagai berikut. Pertama, Unsur-unsur musikal yang membentuk musik suling bambu adalah sebagai berikut. Ritme, secara komposisi ritme/ irama musik suling bambu merupakan irama khas Timor. Melodi, pada suling lagu memainkan melodi utama atau Cantus Frimus (cf), sedangkan suling terompet dan suling bass memainkan melodi filler atau melodi isian sesuai akord. Harmoni, yang berfungsi untuk memainkan akord yaitu suling terompet dan suling bass. Tempo, dalam permainan musik suling bambu sangat relatif tergantung pada lagu yang dibawakan, yang sering digunakan adalah tempo Adante : MM 72-76, Adantino: MM 80-84 dan Moderato: MM 90-104. Penelitian ini dapat memperluas perspektif pembaca tentang keberadaan musik suling bambu dan memberi informasi tentang bentuk dan unsur musikal yang membentuk musik suling bambu di Kabupaten Timor Tengah Utara (TTU).Kata Kunci: Musik suling bamboo; bentuk; dan unsur musikal.